TCP/IP Illustrated - Wright, Gary; Stevens, W. (Addison-Wesley Professional, 1995)
TCP/IP Illustrated , an ongoing series covering the many facets of TCP/IP, brings a highly-effective visual approach to learning about this networking protocol suite. TCP/IP Illustrated, Volume 2 contains a thorough explanation of how TCP/IP protocols are implemented. There isn't a more practical or up-to-date bookothis volume is the only one to cover the de facto standard implementation from the 4.4BSD-Lite release, the foundation for TCP/IP implementations run daily on hundreds of thousands of systems worldwide. Combining 500 illustrations with 15,000 lines of real, working code, TCP/IP Illustrated, Volume 2 uses a teach-by-example approach to help you master TCP/IP implementation. You will learn about such topics as the relationship between the sockets API and the protocol suite, and the differences between a host implementation and a router. In addition, the book covers the newest features of the 4.4BSD-Lite release, including multicasting, long fat pipe support, window scale, timestamp options, and protection against wrapped sequence numbers, and many other topics. Comprehensive in scope, based on a working standard, and thoroughly illustrated, this book is an indispensable resource for anyone working with TCP/IP.